The effectiveness of N-acetylcysteine in alleviating clinical Symptoms of COVID-19 hospitalized patients at Santa Elisabeth Purwokerto General Hospital, Indonesia - Ekowati, Heny; Nadzif, Faradina Qorina; Suryoputri, Masita Wulandari; Endriastuti, Nialiana Endah; Baroroh, Hanif Nasiatul (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2023)
Background: COVID-19 has been associated with increased innate immune system activation, leading to increased mucus production, inflammation, and tissue damage. N-Acetylcystysteine (NAC), an antioxidant and mucolytic, has demonstrated potential as a COVID-19 therapy. Objective: The purpose of this study was to evaluate the effectiveness of NAC on the clinical symptoms of hospitalized COVID-19 patients at Santa Elisabeth Purwokerto General Hospital in Indonesia. Methods: An observational analytical study design was employed, with data collected from the medical records of hospitalized COVID-19 patients at Santa Elisabeth Purwokerto General Hospital over the period of July 2020 to July 2021. The study included 209 patients who met the eligibility criteria. Results: The results indicated that the use of NAC affected the clinical symptoms of cough, oxygen saturation (SPO2), and respiratory rate in patients with mild and moderate degrees of COVID-19 patients (p<0.05). However, it was found not to affect patients with severe degrees of the disease (p>0.05). Conclusion: This study suggests that NAC may be a useful treatment option for patients with mild and moderate COVID-19. Further research is needed to confirm these findings and determine their effectiveness in severe cases.